Contemporary Advances in Innovative and Applicable Information Technology Proceedings of ICCAIAIT 2018 - Mandal, Jyotsna Kumar; Sinha, Devadatta; Bandopadhyay, J.P.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book enriches the literature on different sub-domains of applied information technology. The ICCAIAIT Proceedings presents the high quality research papers presented at ICCAIAIT 2018. The contributions cover the contemporary issues in data analytics, computational intelligence, nature inspired computing, cyber physical systems, cloud computing, social network and intelligent computing on climate change. The volume is an important resource for educationists, academics, scholars and practitioners from both the public and private sectors.
Part 1.Computational Intelligence -- Chapter 1.A Hierarchical Image Cryptosystem Based on Visual Cryptography and Vector Quantization -- Chapter 2.Intelligent Web Service Searching Using Inverted Index -- Chapter 3.Computational Intelligence based Neural Session Key Generation on E-Health System for Ischemic Heart Disease Information Sharing -- Part 2.Circuit System & Devices -- Chapter 4.Computation of Peak Tunneling Current Density in Resonant Tunneling Diode using Self-Consistency Technique -- Chapter 5.Computing Surface Potential and Drain Current in Nanometric Double-Gate MOSFET using Ortiz- Conde Model -- Chapter 6.Comparative Studies on the Performance Parameters of a P-channel Tunnel Field Effect Transistor using Graphene Nanoribbon as channel material with those using other channel materials for Low Power Digital application -- Chapter 7.Implementation of Toffoli Gate using LTEx Module of Quantum-Dot Cellular Automata -- Chapter 8.Study on localized surface plasmon to improvephotonic extinction in solar cell -- Chapter 9.Organic electricity from Zn/Cu-PKL electrochemical cell -- etc.
Keywords: Computational intelligence; Electronic circuits; Data protection; Telecommunication; Computational Intelligence; Electronic Circuits and Systems; Data and Information Security; Communications Engineering, Networks